Kemampuan pemecahan masalah matematis ditinjau dari self-efficacy: Studi korelasional - Fitry Wahyuni; Muhammad Daut Siagian; Ade Evi Fatimah (Mahesa Research Center, 2023)
Problem-solving is one of the mathematical skills needed by students and plays an important role in helping them achieve conceptual understanding in learning mathematics. On the other hand, self-efficacy is also important because it relates to a person's belief in his ability to complete a task or achieve a goal. Based on this, this study aims to examine the relationship between self-efficacy and problem-solving abilities. To achieve the research objectives, the quantitative correlational method was used in this study. Data collection used a survey method to obtain data self-efficacy and students' mathematical problem-solving abilities. Data analysis was performed using inferential statistical analysis to prove the research hypothesis. Hypothesis testing includes analysis of correlation, regression, and coefficients of determination. Based on the results of the study, it can be concluded that there is a moderately positive relationship between self-efficacy and problem-solving abilities. where self-efficacy contributes to problem-solving abilities by 27.8%.